Factors That Predict Involvement in Online Instruction; A Comparison of Full-Time and Part-Time Community College Faculty - Duane Akroyd; Susan Bracken; Bess Patton; Melissa Jackowski (Adult Education Research Conference, 2012)
Community college faculty represent more than one-third of all faculty within postsecondary education institutions and educate nearly half of all first-time college students (Cohen & Brawer, 2008; Gahn & Twombly, 2001; Huber, 1998; Jaeger & Eagan, 2009). Increasingly, two-year institutions are employing more part-time faculty. From 1988 to 1993, the percentage of part-time faculty at public two-year institutions rose from 52% to 62% (U.S. Department of Education, 1997). According to Outcalt (2002), part-time faculty now account for nearly 65% of all community college faculty. Although the use of part-time faculty is increasing in two-year institutions, part-time community college faculty are not treated in the same ways as their full-time counterparts.